Simultaneous pancreas-kidney transplantation: Pro et Contra - Alexandra Mikhailovna Glazunova; Malkhaz Viktorovich Kvaratskheliya; Minara Shamkhalovna Shamkhalova; Marina Vladimirovna Shestakova (Сахарный диабет)
The review addresses the questions of history, clinical features and outcomes of simultaneous pancreas-kidney transplantation in patients with diabetesmellitus type 1. This approach was shown to have positive aspects, such as improvement of glycemic control, rapid normalization and long-termmaintenance of glycated hemoglobin levels, disappearance of hypoglycemic events, and deceleration of coronary artery disease progression resultedin reduced incidence of cardiovascular mortality. Operative risk and post-transplantation complications are also described in details.